Time and uncertainty in resource dilemmas : equilibrium solutions and experimental results - Botelho, Anabela (2012)
Most common pool resource (CPR) dilemmas share two features: they evolve over time and they are managed under environmental uncertainties. We propose a finite-horizon, stochastic, dynamic model that integrates these two dimensions. A distinguishing feature of our model is that the duration of the game is determined endogenously by the players’ collective decisions. In the proposed model, if the resource stock level below which the irreversible event occurs is known in advance, then the optimal resource use coincides with a unique symmetric equilibrium that guarantees survival of the resource. As the uncertainty about the threshold level increases, resource use increases if users adopt decision strategies that quickly deplete the resource stock; however, resource use decreases if they adopt path strategies guaranteeing that the unknown threshold level is never exceeded. Our experimental results show that CPR users frequently implement decision strategies that terminate the game immediately. When the uncertainty about the resource level is reduced, users maintain a positive resource level for a longer duration.